Frequency component analysis of eeg recording on various visual tasks: Steady-state visual evoked potential experiment - Inkaew, Narongrit; Charoenkitkamjorn, Nattaphon; Yangpaiboon, Chongkon; Phothisonothai, Montri; Nuthong, Chaiwat (My University, 2015)
Nowadays, steady-state visual evoked potential (SSVEP) is ongoing in many research topics. It also plays an important role in the response to various visual stimuli such as flickering rate (F), intensity (I), and duty cycle (D). The SSVEPs are practical and useful in research because of its excellent signal-to-noise ratio and relative immunity to artifacts. The application of using SSVEP-based system has been widely succeeded in many disciplines. In this paper, we investigate SSVEP corresponding to the different visual stimulation in terms of frequency component analysis in the four principal frequency bands, i.e., delta (0.1-3.5 Hz), theta (4.0-7.5 Hz), alpha (8.0-13.0 Hz), and beta (14.0-30.0 Hz). Subjects were instructed to fixate LED light source then record associated SSVEP waveform. The variation in displaying of the presentation stimuli during a task was examined. Experimental results showed that the major frequency distribution has been found in theta and alpha bands.
Keywords: EEG; Electroencephalogram; Frequency analysis; SSVEP; Steady-state Visually Evoked Potential; Visual stimuli